Improving Reading Skills In Various Dimensions - Mulki, Farhan Rafi; Rahman, Ahmad Syaeful (Literacy: Journal of Education and Social Science, 2023)
This research explores various reading learning strategies aimed at improving reading skills among students. By adopting a descriptive qualitative approach through literature study, this research identifies and analyzes the effectiveness of the SQ3R method, skimming and scanning techniques, as well as the application of critical and creative reading in educational contexts. Additionally, this research considers the role of technology in reading learning, highlighting how reading learning apps and software can motivate students and support inclusive and adaptive teaching. The findings from this study indicate that the integration of technology in reading instruction not only increases student motivation but also facilitates more personalized and effective learning. A combined approach between extensive and intensive reading has been proven to be effective in enriching reading comprehension and fluency. This study also emphasizes the importance of developing critical and creative reading skills to prepare students to face literacy challenges in the 21st century. The implications of this research offer valuable guidance for educators in designing and implementing comprehensive reading instructional strategies, which align with current educational standards and support the development of effective educational policies.